2018
DOI: 10.1590/0034-7167-2017-0502
|View full text |Cite
|
Sign up to set email alerts
|

Children hospitalized due to maltreatment in the ICU of a Public Health Service

Abstract: ABSRACT Objective: to characterize children hospitalized due to violence in a pediatric ICU in 2011; to relate violence and the mechanisms of trauma with death; to know the contextualization of violence, from the records in the medical records. Method: retrospective cohort, performed in a fi rst aid hospital, Porto Alegre city, in the records of 22 children hospitalized in the ICU due to violence. Quantitative analysis was performed by absolute and relative frequency rates, chi-square and relative risk. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 10 publications
0
5
0
5
Order By: Relevance
“…This study pointed out that girls are more susceptible to suffer some type of sexual abuse, being identified that 19.7% of the women suffered some type Characteristics of violence against children in Porto Alegre Dornelles TM, Macedo ABT, Antoniolli L, Vega EAU, Damaceno AN, Souza SBC of sexual abuse before eighteen years of age, while the male gender presented a prevalence of 7.9%. 17 The data show a 60.6% prevalence of some type of violence in female children. This gender was more susceptible to sexual violence compared to male children.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This study pointed out that girls are more susceptible to suffer some type of sexual abuse, being identified that 19.7% of the women suffered some type Characteristics of violence against children in Porto Alegre Dornelles TM, Macedo ABT, Antoniolli L, Vega EAU, Damaceno AN, Souza SBC of sexual abuse before eighteen years of age, while the male gender presented a prevalence of 7.9%. 17 The data show a 60.6% prevalence of some type of violence in female children. This gender was more susceptible to sexual violence compared to male children.…”
Section: Discussionmentioning
confidence: 94%
“…The prevalence of sexual abuse appears around 20% in girls and 8% in boys. 2,17,18 The World Health Organization (WHO) 32 points out that disabling characteristics, such as some type of disability, do not appear to be an important risk factor for abuse when other factors are considered, as the context of development, the children's living conditions, their family, and the community. 24 We consider that social or family support can contribute so that this vulnerability does not represent a predisposing condition to violence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apesar de o ato violento levar à criança ao hospital deve-se pensar que a repetição deste ato leva à gravidade da lesão. 6 Brazilian Journal of Development, Curitiba, v.7, n.4, p. 41651-41665 apr 2021 Estudo de Farias concluiu que das 498 fichas de notificação analisadas, 60% estavam entre os dois e cinco anos e que a maioria das denúncias partiram da área da saúde. Neste sentido acredita-se que uma das formas de minimizar esses danos seja a intervenção da atenção básica com a tomada de decisão por profissionais das Unidades Básicas de Saúde guiada pela notificação ao Sistema de Informação de Agravos de Notificação (SINAN), que em linhas gerais coleta e dissemina dados referentes ao agravo da condição, entre os quais se destaca os maus-tratos.…”
Section: Introductionunclassified
“…A importância da realização da notificação da violência pelos profissionais de saúde decorre, principalmente, do pacto de silêncio que comumente se faz presente na família, dificultando o enfrentamento da situação. Assim, as vítimas por vergonha, medo, ou por sentirem-se culpadas, não expõe a agressão sofrida, cabendo assim aos profissionais assumirem a responsabilidade em proteger as vítimas e romper com o silêncio ( Santomé, Leal, Mancia & Gomes, 2018) De acordo com a Legislação brasileira, todas as modalidades de violação aos direitos da criança e do adolescente são plausíveis de notificação, seja violência física, psicológica, sexual ou negligência. Mais recentemente, por meio da Portaria MS/GM nº.…”
Section: Introductionunclassified